Increased Phospho-Keratin 8 Isoforms in Colorectal Tumors Associated with EGFR Pathway Activation and Reduced Apoptosis. (31st January 2012) - Arentz, Georgia; Chataway, Tim; Condina, Mark R.; Price, Timothy J.; Hoffmann, Peter; Hardingham, Jennifer E.
Abstract : Hyperphosphorylated keratin (K) 8 acts as a phosphate "sponge" for stress-activated protein kinases thereby inhibiting pro-apoptotic molecules and thus apoptosis. MAP kinase/ERK1 has increased activity in colorectal cancer (CRC) and is known to phosphorylate K8. The aims were to identify the K8 isoforms abundantly present in colon tumors, using 2D difference gel electrophoresis (DIGE), to identify the modifications using mass spectrometry, and to validate the differential abundance of these isoforms in tumors relative to matched normal mucosae. 2D DIGE showed 3 isoforms of K8 significantly increased in tumor ≥2-fold in 6/8 pairs. Metal oxide affinity chromatography mass spectrometry and bioinformatics were used to identify phosphorylated serine residues. Levels of PS24, PS432, and PS74 by western blotting were found to be significantly increased in tumor versus matched normal. Blocking of EGFR signaling in Caco2 cells showed a significant decrease (P < 0.0001 ) in K8 PS74 and PS432 levels by 59% and 66%, respectively, resulting in increased apoptosis.